Influência do tamanho e teor de agregado nas propriedades do concreto permeável - Jahn, Lucas Claudir (2016)
The unplanned urban expansion brings with it an increase impermeabilization of the soil surface through buildings, streets, sidewalks that end up affecting the water cycle and causing flood. An alternative to solve these problems is the construction of floors with permeable concrete that help to restoring soil infiltration capacity. This research aimed to study the influence of the size and aggregate content in pervious concrete properties used as permeable coating layer in permeable pavements. For this were performed assays with six different mixtures with varying size and proportion of aggregate in the mix. The mixture characterization was done based on the following assays: slump test, Vebe time, compressive strength, diametric compression strength, water absorption, void ratios, bulk density and dynamic modulus of elasticity through the impulse excitation technique. To determine the hydraulic conductivity (permeability) we used a variable load permeameter. From the results it was observed that the permeability coefficient of the mixtures analyzed in the study were high, above the values established by the standard NBR 16416. Regarding to resistance, all mixtures showed good performance traction in flexion, getting the minimum requirements of the standard, although the resistance to relative compression have obtained values below the minimum specified in the standard. The mixture with better performance and potential for use in permeable paving was M5B1, since the high permeability (1,27 cm / s) and minimum traction strength within the standard NBR 16416.